2005
DOI: 10.1007/s10194-005-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinic–based study of family history of vascular risk factors and migraine

Abstract: The objective was to evaluate the presence of a positive family history (FH) of vascular risk factors between patients with migraine with aura (MA) and migraine without aura (MO), and in chronic migraine (CM) compared to other headache types. As migraine patients are typically too young to have developed vascular events, studying older relatives of migraine patients may be a practical means of evaluating associations between vascular risk factors and migraine. A cross-sectional study of a clinicbased sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Furthermore, ischemic encephalic vascular accidents (EVAs) and migraine are associated 23 . Ischemic EVA is more prevalent in chronic migraine than in the general population; comparatively, episodic migraine shows greater comorbidity with ischemic EVA than chronic migraine 24 , which is also significantly less associated with family history of EVA than episodic migraine 25 .…”
Section: Cerebrovascular Diseasesmentioning
confidence: 92%
“…Furthermore, ischemic encephalic vascular accidents (EVAs) and migraine are associated 23 . Ischemic EVA is more prevalent in chronic migraine than in the general population; comparatively, episodic migraine shows greater comorbidity with ischemic EVA than chronic migraine 24 , which is also significantly less associated with family history of EVA than episodic migraine 25 .…”
Section: Cerebrovascular Diseasesmentioning
confidence: 92%
“…(24) La migraña crónica también se asocia significativamente menos a la historia familiar de AVE que la migraña episódica. (25)…”
Section: Enfermedades Cerebrovasculares Enfermedades Cerebrovasculares Enfermedades Cerebrovasculares Enfermedades Cerebrovasculares Enfeunclassified
“…However, the main limitation to the risk factors hypothesis is that in the above reported studies as in other studies most of the vascular risk factors were present in the multivariate model which showed the association between migraine and cerebrovascular and cardiovascular diseases [ 70 , 88 , 89 , 103 ]. In addition, several studies indicated that the migraine–stroke association was present in the absence of traditional vascular risk factors and that the type of stroke was less frequently a large-vessel stroke or a small-vessel stroke with respect to the general stroke population [ 62 , 104 ].…”
Section: Migraine and Cerebrovascular And Cardiovascular Diseasesmentioning
confidence: 99%